2014
DOI: 10.1007/s00414-014-0964-6
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem CT compared to autopsy in children; concordance in a forensic setting

Abstract: • The case mix is an important predictor for the concordance between PMCT and autopsy. • In case of an unnatural death, 72--81% of PMCT results matches autopsy results. • In case of a natural death, 0% of PMCT results matches autopsy results. • If no cause of death is identified with autopsy, 98% of PMCT results concurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…According to the forensic literature on children, many lesions that are important for the determination of cause of death can be detected by PMCT; in 67 % of cases, PMCT identified the same cause of death as conventional autopsy [20]. More specifically, it has been reported that signs of pulmonary aspiration with consequent asphyxia, which have often been described in cases of sudden infant death, can be detected by performing an external examination in combination with CT. Infectious diseases that occur frequently in children [15,24] can also often be detected by PMCT, with characteristic findings on abdominal and thoracic CT images.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the forensic literature on children, many lesions that are important for the determination of cause of death can be detected by PMCT; in 67 % of cases, PMCT identified the same cause of death as conventional autopsy [20]. More specifically, it has been reported that signs of pulmonary aspiration with consequent asphyxia, which have often been described in cases of sudden infant death, can be detected by performing an external examination in combination with CT. Infectious diseases that occur frequently in children [15,24] can also often be detected by PMCT, with characteristic findings on abdominal and thoracic CT images.…”
Section: Discussionmentioning
confidence: 97%
“…Most studies that compared the findings of imaging examinations with those of conventional autopsy included adults only [5,[16][17][18][19]. Moreover, the few studies that evaluated pediatric cases [20,21] were specific to sudden infant [15] or post-traumatic death [22]. Thus, the purpose of this study was to compare the findings of postmortem CT (PMCT) with those of forensic conventional autopsy in a group of children who died of different causes and evaluate its potential usefulness in non-medicolegal situations.…”
Section: Introductionmentioning
confidence: 97%
“…Although not publicly available, this database enables data analysis in pre-and post-mortem cases and has proved to be a useful source for retrospective research and scientific collaboration [9,13,19].…”
Section: Limitations and Privacy Issuesmentioning
confidence: 99%
“…This is particularly useful where sanitised images are required for a jury in medicolegal proceedings, or to show family members when explaining the cause of death [ 6 ]. Although few publications relate to the diagnostic accuracy rates of paediatric postmortem CT, those published report reasonable concordance rates with autopsy of between 57.1% and 83.3% [ 4 , 5 , 7 , 8 ], particularly for musculoskeletal abnormalities such as fractures.…”
Section: Introductionmentioning
confidence: 99%